Digital Promotion for Islamic Broadcasting and Education: A Reproductive Health Perspective through Ning Mila's Haid Class in NU Online YouTube. - Sumadi; Lilis Nurteti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Reproductive health is a fundamental issue in people's lives. But the fact is that people in general do not have sufficient awareness about the importance of reproductive health. The main factor is the lack of reproductive health information received by the community. In the digital era, YouTube has become a cheap and effective social media for disseminating reproductive health knowledge and information. Using qualitative methods and descriptive analysis, this study focuses on the content of Ning Mila's Haid Class on Youtube Chane Nahdlatul Ulama (NU). Reproductive health is important to be promoted digitally through digital platforms via social media. The combination of religion (Islam) and reproductive health is the strength of Haid Ning Mila's content. Through YouTube, Islamic education and broadcasting with a reproductive health perspective can simultaneously be carried out together. In the future, the content of Ning Mila's menstruation class can be an alternative source of information and education on reproductive health to fulfill people's rights.